Multi-disciplinary advancement in open source software and processes - Koch, Stefan, 1974- (Information Science Reference, 2011)
"This book reviews the development, design, and use of free and open source software, providing relevant topics of discussion for programmers, as well as researchers in human-computer studies, online and virtual collaboration, and e-learning"--Provided by publisher.